2011
DOI: 10.3174/ajnr.a2501
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Locoregional Control in Head and Neck Squamous Cell Carcinoma with Serial CT Perfusion during Radiotherapy

Abstract: BACKGROUND AND PURPOSE:Tumor hypoxia is a known factor of radioresistance in HNSCC. CTP is a noninvasive method of measuring tumor perfusion in vivo. The purpose of our study was to determine serial changes in tumor perfusion in HNSCC during a course of RT by using CTP and to correlate tumor perfusion measurements to LRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
4
35
1
1
Order By: Relevance
“…Gandhi et al 16 (after 1 cycle of induction chemotherapy; 3-4 weeks after the treatment start) for the TBF measurement compared with the present study and the study by Truong et al 14 These descriptions of TBF decreases in patients with good treatment responses also showed the same trend as that seen in our present patients with PR. In regard to these findings, we had several hypotheses.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Gandhi et al 16 (after 1 cycle of induction chemotherapy; 3-4 weeks after the treatment start) for the TBF measurement compared with the present study and the study by Truong et al 14 These descriptions of TBF decreases in patients with good treatment responses also showed the same trend as that seen in our present patients with PR. In regard to these findings, we had several hypotheses.…”
Section: Discussionsupporting
confidence: 74%
“…Truong et al 14 reported that an initial increase in TBF in the early treatment period (2 weeks after the treatment started) in patients undergoing chemoradiotherapy predicted a good treatment result. The results of their report showed the same trend as that seen in the present study in regard to the patients who achieved SD status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were increased with the number of fractions delivered, thus, were radiation induced. Similar CTN changes were not observed (,3%) in the spinal cords and NSTs, where radiation doses were substantially lower than those in the GTVs and parotid glands (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy vs 75-65 Gy in maximum doses). The observed CTN change was highly patient specific.…”
Section: Discussionmentioning
confidence: 57%
“…The mechanism behind this CTN change is largely unknown. It has been reported that the pre-treatment tumour blood flow and capillary permeability in patients who achieved locoregional control were significantly higher than in those with treatment failure 24 and that low perfusion of head and neck cancer was associated with higher rates of local failure of RT. 25 Tumours that demonstrated CTN reduction may represent regions of improved oxygenation and sensitivity to radiationinduced damages.…”
Section: Discussionmentioning
confidence: 99%